Clear cell sarcomas of the kidney are characterised by BCOR gene abnormalities, including exon 15 internal tandem duplications and BCOR–CCNB3 gene fusion. Issue 2 (30th October 2017) - Wong, Meng K; Ng, Cedric C Y; Kuick, Chik H; Aw, Sze J; Rajasegaran, Vikneswari; Lim, Jing Q; Sudhanshi, Jain; Loh, Eva; Yin, Minzhi; Ma, Jing; Zhang, Zhongde; Iyer, Prasad; et al.
Abstract : Aims: Clear cell sarcoma of the kidney (CCSK) is a rare paediatric renal malignant tumour. The majority of CCSKs have internal tandem duplications (ITDs) of the BCOR gene, whereas a minority have the YWHAE–NUTM2 gene fusion. A third 'double‐negative' (DN) category comprises CCSKs with neither BCOR ITDs nor YWHAE–NUTM2 fusion. The aim of this study was to characterise 11 histologically diagnosed CCSKs immunohistochemically (with CCND1, BCOR and CCNB3 stains) and genetically. Methods and results: By next‐generation sequencing, 10 cases (90.9%) had BCOR exon 15 ITDs, with positive BCOR immunoreactivity being found in four (36%) or eight (72%) cases, depending on the antibody clone. By reverse transcription polymerase chain reaction, none had the YWHAE–NUTM2 fusion. The DN case had a BCOR–CCNB3 fusion and strong nuclear CCNB3 and BCOR immunoreactivity. Quantitative polymerase chain reaction showed markedly elevated BCOR expression in this case, whereas BCOR ITD cases had lower levels of elevated BCOR expression. Conclusions: The majority of the CCSKs in our cohort had BCOR ITDs, and none had the YWHAE–NUTM2 fusion. We verified the strong, diffuse cyclin D1 (CCND1) immunoreactivity in CCSKs described in recent reports. BCOR immunoreactivity was not consistently positive in all CCSKs with BCOR ITDs, and therefore cannot be used as a diagnostic immunohistochemical stain to identify BCOR ITD cases. The DN case was a BCOR–CCNB3 fusion sarcoma. BCOR–CCNB3 sarcoma is typically a primary bone sarcoma affecting male adolescents, and this is the first report of it presenting in a kidney of a young child as a CCSK. The full spectrum of DN CCSKs awaits more comprehensive characterisation.